The effectiveness of analytical chemistry problem based learning model on student learning outcomes - Marnida Yusfiani; Ahyani Ridhayani Lubis; Fuadaturrahmah Fuadaturrahmah; Mei Salwa Siregar (Pascasarjana Universitas Negeri Medan, 2022)
This study aims to get a value of the effectiveness of students in learning analytical chemistry. The subjects carried out in this study were 30 Tanjungbalai Polytechnic students. The method used is to analyze the pre-test and post-test as well as data on the frequency distribution of the G factor. From the results of the study it can be concluded as follows 1). The value of the pre-test results showed that out of 30 students there was 1 person (3.33%) with the highest score with a score of 74. For 29 people (97.67%) were declared not to have passed because the score was below 74. 2). The standard deviation value is 6.33 with a variance of 40.110. 3). the posttest score of 5 people with the highest score of 90 with a percentage of 16.67%, and 83.33% showed a score below 90 and passed the PBL Chemistry Analysis lesson. The conclusion from the results of the increased learning outcomes in the analytical chemistry course was obtained that the g factor value was 0.56 in the moderate category and a percentage of 56.16% in the quite effective category.Keywords: Analytical chemistry; Learning improvement results; PBL model; Learning outcomes